NGHIÊN CỨU ĐỘNG LỰC HỌC THIẾT BỊ BÀN ĐẦM RUNG HỖN HỢP BÊ TÔNG PHỤC VỤ TRONG PHÒNG THÍ NGHIỆM - VI NGUYEN, TIEN; VU DANG, DINH (Tạp chí Khoa học Công nghệ Hàng hải, 2022)
The article presents the scientific basis for studying the influence of the eccentric shaft rotation speed on the compaction quality of the concrete mixture. In this regard, the dynamic model of the table-type concrete vibrator is first developed and solved by the numerical method. Then, the reasonable eccentric shaft rotation speed is estimated to improve the compaction quality of fresh concrete materials. In addition, the observed results serve as the guideline and suggestions for designing and using such types of construction machines.